Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Get accurate and detailed answers to your questions from a dedicated community of experts on our Q&A platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
You need to work this out using pythagoras' theorem.
Csquared=Asquared+Bsquared
But you are finding out A, not C, so you must rearrange the equation.
Asquared=Csquared-Bsquared
Asquared= 484-256
Asquared=228
A=Square root of 228
A=15 :)
Csquared=Asquared+Bsquared
But you are finding out A, not C, so you must rearrange the equation.
Asquared=Csquared-Bsquared
Asquared= 484-256
Asquared=228
A=Square root of 228
A=15 :)
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.